Stadt-Land-Unterschiede im Angebot von Lebensstilberatung zur Prävention kardiovaskulärer Erkrankungen in der Hausarztpraxis: Ergebnisse einer bundesweiten Hausärztebefragung = Differences in the provision of lifestyle counseling for cardiovascular disease prevention between urban and rural regions in Germany : findings from a national survey of primary care physicians - Görig, Tatiana; Diehl, Katharina; Herr, Raphael; Mayer, Manfred; Schneider, Sven (Das Gesundheitswesen, 2016)
Aims: In Germany, shortages in primary care physicians (PCPs) were reported in some rural regions. In this paper, we explored if regional differences in the distribution of PCPs are associated with the provision of lifestyle counseling in primary care. Methods: In a nationwide study, a total of 4,074 randomly selected PCPs were asked about provision of lifestyle counseling to their patients, their attitudes, and perceived barriers. Results: PCPs from rural regions provided less frequently lifestyle advice for cardiovascular disease prevention. Compared to their colleagues in urban areas, more PCPs from rural regions believed that were inadequately qualified for the lifestyle counseling and that they had been less successful in helping patients to modify their lifestyles. Physicians from rural practices named more often than PCPs from urban practices a lack of adherence by the patients (65 vs. 57%), insufficient opportunities to collaborate with providers of preventive services (62 vs. 55%), and lack of time (66 vs. 52%; all p<0.001) as barriers in providing patients with lifestyle counseling. Conclusion: Taking into account the expected increased shortages in PCPs in rural regions, the results show the need for targeted interventions for improving lifestyle counseling in rural practices.
Gesehen am 18.07.2019
Online-Publikation: 30.11.2015